Peran Guru dalam Pembentukan Karakter Anak Usia Dini di TK Putra Mandiri 1 - Eko Tri Wahyuti; Eka Danik Prahastiwi (MASALIQ, 2026)
Character education in early childhood is an important aspect of shaping children’s behavior and personality from an early age. This study aims to describe the role of teachers in shaping early childhood character at TK Putra Mandiri 1, identify the character values instilled, and explain the strategies used in implementing character education. This study employed a descriptive qualitative approach with a case study design. The research informants consisted of the principal and teachers who were directly involved in the learning process. Data were collected through observation, interviews, and documentation and were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that teachers play an important role as role models, guides, motivators, and facilitators in shaping early childhood character. The character values instilled included religiosity, discipline, honesty, responsibility, independence, social care, politeness, hard work, and self-confidence. Character formation was carried out through habituation activities, exemplary conduct, worship practices, learning through play, and group learning activities. In addition, school culture and cooperation between teachers and parents also supported the success of character education at school. Nevertheless, the implementation of character education still faces obstacles, such as differences in family backgrounds and the limited involvement of some parents in supporting children’s character habituation at home. The conclusion of this study affirms that strengthening the role of teachers, school culture, and collaboration with parents are important factors in shaping positive character in early childhood. These findings contribute to the development of character education at the early childhood education level and serve as a reference for early childhood education institutions in designing more effective and sustainable character education strategies.